Metal nitride, film, laminate, element, device, method for manufacturing film, magnetic tunnel junction element and magnetic device

By employing a metal nitride with a wurtzite structure that can be magnetized by an electric field, the power consumption of magnetic tunnel junctions is reduced, addressing the high power requirements of existing MTJ technologies.

JP2025066629APending Publication Date: 2025-04-23SUMITOMO CHEM CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024064148
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-10-11
Filing Date
2024-04-11
Publication Date
2025-04-23

AI Technical Summary

Technical Problem

Magnetic tunnel junctions (MTJs) require a large amount of power to change electrical resistance using an external magnetic field, leading to high power consumption.

Method used

The use of a specific metal nitride with a wurtzite structure, formulated as Z1-xMxWyN1-y, where Z is Al, In, or Ga, M is Sc, B, or other elements, and W is O, S, or other elements, which can be magnetized by an electric field rather than an external magnetic field, reducing power consumption.

Benefits of technology

This approach significantly reduces the power consumption of MTJs by eliminating the need for an external magnetic field, thereby minimizing Joule heat losses and improving the efficiency of MTJ devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025066629000001_ABST
    Figure 2025066629000001_ABST
Patent Text Reader

Abstract

To provide: a metal nitride, a film, a laminate, an element, and a device, capable of reducing power consumption of a magnetic tunnel junction; a method for manufacturing the film; a magnetic tunnel junction element; and a magnetic device.SOLUTION: A metal oxide has a wurtzite-type structure and is represented by the general formula: Z1-xMxWyN1-y, where: Z is at least one element selected from the group consisting of Al, In, and Ga; M is at least one element selected from the group consisting of Sc, B, Gd, Cr, Zn, Y, La, Ce, Pr, Nd, Sm, Eu, Tb, Dy, Ho, Er, Tm, Yb, Ti, Hf, and Zr; W is at least one element selected from the group consisting of O, S, Se, F, Cl, Br, and I; 0<x≤0.45; and 0<y≤0.4; and the metal oxide is not an n-type semiconductor.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to metal nitrides, films, stacks, elements, devices, methods for manufacturing films, magnetic tunnel junction elements, and magnetic devices. [Background technology]

[0002] Magnetic tunnel junctions (MTJs) are known (for example, see Patent Document 1 or Patent Document 2). MTJs exhibit a huge magnetoresistance effect at room temperature, and are therefore used in magnetic heads and magnetic random access memories (MRAMs) mounted in hard disk drives (HDDs). MTJs have a structure in which an insulating layer is disposed between two ferromagnetic layers. Because the insulating layer is very thin, a minute current (tunnel current) flows between the two ferromagnetic layers due to the tunnel effect. When the two ferromagnetic layers are parallel to each other, the electrical resistance of the MTJ decreases and the tunnel current increases. On the other hand, when the two ferromagnetic layers are antiparallel to each other, the electrical resistance of the MTJ increases and the tunnel current decreases. In a device employing an MTJ, the magnetization direction of one ferromagnetic layer is fixed by an antiferromagnetic layer, and the magnetization direction of the other ferromagnetic layer can be freely reversed, thereby changing the electrical resistance. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2014-229706 A [Patent Document 2] JP 2022-069247 A [Patent Document 3] JP 2007-261883 A [Non-patent literature]

[0004] [Non-Patent Document 1] HC Lee, “Influence of sputtering pressure on the microstructure evolution of AlN thin films prepared by reactive sputtering”, Thin Solid Films, Volume 261, Issues 1-2, 1 June 1995, Pages 148-153 Summary of the Invention [Problem to be solved by the invention]

[0005] In the above-mentioned MTJ, a large amount of power is required to change the electrical resistance using an external magnetic field, so there is a demand for reducing power consumption.

[0006] An object of the present disclosure is to provide a metal nitride, a film, a stack, an element, a device, a method for manufacturing a film, a magnetic tunnel junction element, and a magnetic device that enable low power consumption of an MTJ. [Means for solving the problem]

[0007] The present inventors have conducted extensive research to solve the above problems and have found that a specific metal nitride having a wurtzite structure enables low power consumption in an MTJ, thus arriving at the present invention.

[0008] [1] It has a wurtzite structure, General formula Z 1-x M x W y N 1-y It is expressed as Z is at least one element selected from the group consisting of Al, In, and Ga; M is at least one element selected from the group consisting of Sc, B, Gd, Cr, Zn, Y, La, Ce, Pr, Nd, Sm, Eu, Tb, Dy, Ho, Er, Tm, Yb, Ti, Hf, and Zr; W is at least one element selected from the group consisting of O, S, Se, F, Cl, Br, and I, 0 < x ≤ 0.45 and 0 < y ≤ 0.4, It is not an n-type semiconductor, A metal nitride. [2] The metal nitride according to [1], wherein Z is Al. [3] The metal nitride according to [1], wherein Z is In. [4] The metal nitride according to [1], wherein Z is Ga. [5] The metal nitride according to any one of [1] to [4], wherein M is Sc. [6] The metal nitride according to any one of [1] to [4], wherein M is B. [7] The metal nitride according to any one of [1] to [6], wherein W is O. [8] The metal nitride according to any one of [1] to [6], wherein W is S. [9] The metal nitride according to any one of [1] to [6], wherein W is Se.

[10] A film comprising the metal nitride according to any one of [1] to [9].

[11] The film according to

[10] , and A conductive layer provided on the film, and a laminate comprising the same.

[12] An element comprising the laminate according to

[11] .

[13] A device comprising the element according to

[12] .

[14] A method for manufacturing the film according to

[10] , A method for manufacturing a film, comprising a sputtering step.

[15] A first ferromagnetic layer which is a magnetization fixed layer, and A second ferromagnetic layer which is a magnetization free layer, and A tunnel insulating layer interposed between the first ferromagnetic layer and the second ferromagnetic layer, A metal nitride layer provided on the first ferromagnetic layer, A first conductive layer provided on the metal nitride layer, and comprising: The metal nitride layer, Has a wurtzite structure, General formula Z 1-x M x W y N 1-y Represented by, Z is at least one element selected from the group consisting of Al, In, and Ga, M is at least one element selected from the group consisting of Sc, B, C, Si, Gd, Cr, Zn, Y, La, Ce, Pr, Nd, Sm, Eu, Tb, Dy, Ho, Er, Tm, Yb, Ti, Hf, and Zr, W is at least one element selected from the group consisting of O, S, Se, F, Cl, Br, and I, 0 < x ≤ 0.45 and 0 < y ≤ 0.4, Magnetic tunnel junction element.

[16] The magnetic tunnel junction element according to

[15] , wherein Z is Al.

[17] The magnetic tunnel junction element according to

[15] , wherein Z is In.

[18] The magnetic tunnel junction element according to

[15] , wherein Z is Ga.

[19] The magnetic tunnel junction element according to any one of

[15] to

[18] , further comprising a second conductive layer provided between the second ferromagnetic layer and the metal nitride layer.

[20] A magnetic device comprising the magnetic tunnel junction element according to any one of

[15] to

[19] .

[21] The magnetic device according to

[20] , which is a magnetic random access memory.

[22] A film containing a metal nitride, A protective layer covering the surface of the film, and comprising: The metal nitride is of a wurtzite-type structure and is represented by the general formula Z 1-x M x W y N 1-y where Z is at least one element selected from the group consisting of Al, In, and Ga; M is at least one element selected from the group consisting of Sc, B, C, Si, Gd, Cr, Zn, Y, La, Ce, Pr, Nd, Sm, Eu, Tb, Dy, Ho, Er, Tm, Yb, Ti, Hf, and Zr; W is at least one element selected from the group consisting of O, S, Se, F, Cl, Br, and I; 0 < x ≦ 0.45 and 0 < y ≦ 0.4; The protective layer contains an oxide of at least one metal element selected from the group consisting of Al, Si, and Ti, a nitride of the metal element, an oxynitride of the metal element, or amorphous silicon. A laminate.

[23] The laminate according to

[22] , wherein Z is Al.

[24] The laminate according to

[23] , wherein Z is In.

[25] The laminate according to

[24] , wherein Z is Ga.

[26] A magnetic device including the laminate according to any one of

[22] to

[25] . [Advantages of the Invention]

[0009] According to one aspect of the present disclosure, there are provided a metal nitride, a film, a laminate, an element, a device, a method for manufacturing a film, a magnetic tunnel junction element, and a magnetic device that enable power consumption reduction of an MTJ. [Brief Description of the Drawings]

[0010] [Figure 1] FIG. 1 is a cross-sectional view showing an MTJ element according to an embodiment. [Diagram 2]FIG. 2 is a cross-sectional view showing a single cell of the MRAM according to the embodiment. [Diagram 3] FIG. 3 is a cross-sectional view showing an MTJ element according to a modified example. [Figure 4] FIG. 4 is a diagram for explaining a method for evaluating the Al0.7Sc0.3O0.05N0.95 film using an AFM. [Diagram 5] Fig. 5(a) is an explanatory diagram of a write region and a write voltage, and Fig. 5(b) is an MFM image showing the magnetization state after writing. [Figure 6] Fig. 6(a) is an explanatory diagram of the write region and the write voltage, Fig. 6(b) is an AFM image showing the surface shape after writing, and Fig. 6(c) is an MFM image of the film showing the magnetization state after writing. [Figure 7] 7(a) is a graph showing the magnetization curve of the Al0.7Sc0.3O0.05N0.95 film, and FIG. 7(b) is a graph showing the magnetization curve of the Al0.7Sc0.3O0.2N0.8 film. [Figure 8] FIG. 8 shows the results of X-ray diffraction of the AlScN film. [Figure 9] FIG. 9 is a graph showing the magnetization curve of the Al0.7Sc0.3OyN1-y film. [Figure 10] FIG. 10 is a graph showing the relationship between the oxygen substitution amount and the saturation magnetization amount. [Figure 11] FIG. 11 is a graph showing the change in saturation magnetization over time. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, embodiments of the present disclosure will be described in detail with reference to the accompanying drawings. In the description of the drawings, the same or corresponding elements are denoted by the same reference numerals, and duplicated descriptions will be omitted.

[0012] (Metal nitrides) The metal nitride according to this embodiment has a wurtzite structure and is represented by the general formula Z 1-x M x W y N 1-yIt is represented by. Here, Z, M, W, and N are as follows. Z: At least one element selected from the group consisting of Al, In, and Ga M: At least one element selected from the group consisting of Sc, B, C, Si, Gd, Cr, Zn, Y, La, Ce, Pr, Nd, Sm, Eu, Tb, Dy, Ho, Er, Tm, Yb, Ti, Hf, and Zr W: At least one element selected from the group consisting of O, S, Se, F, Cl, Br, and I Also, 0 < x ≤ 0.45 and 0 < y ≤ 0.4. It may be 0 < y ≤ 0.3.

[0013] The metal nitride may be, for example, AlScON. In this case, the chemical composition ratio of Al atoms is, for example, 30% or more and 50% or less. The chemical composition ratio of Sc atoms is, for example, 0% or more and 40% or less. The chemical composition ratio of O atoms is, for example, 0% or more and 30% or less. The chemical composition ratio of N atoms is, for example, 30% or more and 50% or less. The ratio of Sc atoms to the sum of Al atoms and Sc atoms may be, for example, 0.1 or more and 0.45 or less (Sc / (Al + Sc) = 0.1 to 0.45), and may also be 0.1 or more and 0.3 or less (Sc / (Al + Sc) = 0.1 to 0.3). The ratio of O atoms to the sum of N atoms and O atoms may be, for example, 0.1 or more and 0.4 or less (O / (N + O) = 0.1 to 0.4), and may also be 0.1 or more and 0.3 or less (O / (N + O) = 0.1 to 0.3).

[0014] Metal nitrides are not n-type semiconductors, but are, for example, p-type semiconductors or dielectrics. Metal nitrides are, for example, ferroelectrics. It can be confirmed that metal nitrides are not n-type semiconductors, for example, by measuring the Hall effect. The Hall effect is a phenomenon in which, when a magnetic field perpendicular to the current is applied to an object through which a current flows, a potential difference (Hall voltage) occurs in a direction perpendicular to both the current and the magnetic field. It can be confirmed that a metal nitride is not an n-type semiconductor by measuring the direction (sign) of the Hall voltage. It can be confirmed that a metal nitride is not an n-type semiconductor, for example, by vapor-depositing a metal on the surface of the metal nitride and measuring the current-voltage characteristics, and by not confirming rectification, or by not confirming depletion of the metal nitride from the capacitance-voltage characteristics.

[0015] Low-resistance n-type AlN (aluminum nitride) crystal is described in Patent Document 3. The metal oxide according to this embodiment differs from the AlN crystal described in Patent Document 3 in that it is not an n-type semiconductor.

[0016] The inventors have found that the metal nitride according to this embodiment is a magnetic material that is magnetized by applying an electric field. As described above, a large amount of power is required to change the electrical resistance of the MTJ using an external magnetic field. Normally, an external magnetic field is generated by passing a current through a coil, but this generates loss due to Joule heat, such as heat generated by the coil. In contrast, the metal nitride according to this embodiment can be magnetized by an electric field without using an external magnetic field. Therefore, the generation of Joule heat can be suppressed, and the power consumption of the MTJ can be reduced.

[0017] (MTJ element) Fig. 1 is a cross-sectional view showing an MTJ element according to the embodiment. As shown in Fig. 1, the MTJ element 1 according to the embodiment is an element including a ferromagnetic layer 101 (first ferromagnetic layer), a tunnel insulating layer 102, a ferromagnetic layer 103 (second ferromagnetic layer), a conductive layer 104 (second conductive layer), a metal nitride layer 105 (film), and a conductive layer 106 (first conductive layer). The MTJ element 1 has a layered structure in which these layers are stacked in order. The MTJ element 1 is also an example of an element according to this embodiment.

[0018] The ferromagnetic layer 101 and the ferromagnetic layer 103 are disposed with the tunnel insulating layer 102 sandwiched therebetween. The ferromagnetic layer 101 and the ferromagnetic layer 103 are provided adjacent to the tunnel insulating layer 102. The ferromagnetic layer 101 is a magnetization fixed layer (reference layer). In the ferromagnetic layer 101, the magnetization direction is fixed in a predetermined direction. The ferromagnetic layer 103 is a magnetization free layer (memory layer). In the ferromagnetic layer 103, the magnetization direction can be easily changed by magnetization rotation.

[0019] The ferromagnetic layers 101 and 103 include a ferromagnetic material. Examples of the ferromagnetic material include ferromagnetic metals such as iron (Fe), cobalt (Co), an FeCo alloy, and a CoFeB alloy, and ferromagnetic half-metals. The ferromagnetic layers 101 and 103 may include the same ferromagnetic material or different ferromagnetic materials.

[0020] The tunnel insulating layer 102 is interposed between the ferromagnetic layer 101 and the ferromagnetic layer 103. The tunnel insulating layer 102 electrically and magnetically separates the ferromagnetic layer 101 and the ferromagnetic layer 103. The tunnel insulating layer 102 includes an insulator. Examples of the insulator include magnesium oxide (MgO), aluminum oxide (Al2O3), or a mixture of these materials.

[0021] The stack 10 including the ferromagnetic layer 101, the tunnel insulating layer 102, and the ferromagnetic layer 103 forms an MTJ. That is, when the magnetization direction of the ferromagnetic layer 103, which is the magnetization free layer, is the same as the magnetization direction of the ferromagnetic layer 101, which is the magnetization fixed layer (parallel state), the electrical resistance of the MTJ is low, and when they are opposite (antiparallel state), the electrical resistance of the MTJ is high.

[0022] The thickness of the ferromagnetic layer 101 is, for example, from several atomic layers to 100 nm. The thickness of the tunnel insulating layer 102 is such that carriers can tunnel in the thickness direction, and is, for example, 1 nm or more and 2 nm or less. The thickness of the ferromagnetic layer 103 is, for example, 1 nm or more and 10 nm or less. The coercive force of the ferromagnetic layer 101 is greater than that of the ferromagnetic layer 103. An antiferromagnetic layer may be further provided on the side of the ferromagnetic layer 101 opposite the tunnel insulating layer 102. The antiferromagnetic layer is magnetically coupled to the ferromagnetic layer 101, thereby improving the coercive force of the ferromagnetic layer 101.

[0023] The ferromagnetic layer 101 and the ferromagnetic layer 103 are, for example, perpendicular magnetization films magnetized perpendicular to the film surface. The ferromagnetic layer 101 and the ferromagnetic layer 103 are magnetized in the perpendicular upward or downward direction. In the MTJ element 1, the ferromagnetic layer 101 and the ferromagnetic layer 103 are made of ferromagnetic metals such as iron (Fe), cobalt (Co), an FeCo alloy, or a CoFeB alloy, or a ferromagnetic half metal, and the tunnel insulating layer 102 is made of magnesium oxide, aluminum oxide, or a mixture of these materials, and the ferromagnetic layer 101 and the ferromagnetic layer 103 are realized by utilizing the interface magnetic anisotropy. The materials of the ferromagnetic layer 101, the tunnel insulating layer 102, and the ferromagnetic layer 103 may be other combinations of materials as long as they can realize perpendicular magnetization.

[0024] The ferromagnetic layer 101, the tunnel insulating layer 102, and the ferromagnetic layer 103 are formed by, for example, a sputtering method, an atomic layer deposition method, or an ion plating method, with the sputtering method being preferred.

[0025] The conductive layer 104 is provided on the ferromagnetic layer 103. The conductive layer 104 is provided adjacent to the ferromagnetic layer 103. The conductive layer 104 is provided between the ferromagnetic layer 103 and the metal nitride layer 105. The conductive layer 104 includes a conductive material. Examples of the conductive material include titanium nitride (TiN), titanium (Ti), tungsten nitride (WN), tungsten (W), tantalum nitride (TaN), and tantalum (Ta). The conductive layer 104 may be provided on the ferromagnetic layer 103 via a smoothing layer. The smoothing layer is made of, for example, Ta.

[0026] The metal nitride layer 105 is provided on the conductive layer 104. The metal nitride layer 105 is provided in contact with the conductive layer 104. The metal nitride layer 105 is interposed between the conductive layer 104 and the conductive layer .

[0027] The metal nitride layer 105 is a film containing the above-mentioned metal nitride. The metal nitride layer 105 is also an example of a film according to this embodiment. The MTJ element 1 includes the metal nitride layer 105, so that low power consumption is possible. The metal nitride layer 105 is, for example, a polycrystalline film. Being polycrystalline, the quality can be easily controlled and the film can be stably and inexpensively manufactured.

[0028] The crystal grain size of the polycrystalline film is, for example, preferably 5 nm to 200 nm, more preferably 5 nm to 50 nm. The crystal grain size is, for example, an average crystal grain size measured by X-ray diffraction or cross-sectional transmission electron microscope observation. For example, in X-ray diffraction, the crystal grain size can be estimated from the crystallite size using Scherrer's formula that utilizes the half-width of the diffraction signal and the X-ray wavelength, and in cross-sectional transmission electron microscope observation, it can be evaluated by obtaining a dark-field image. The crystal grains are, for example, plate-shaped.

[0029] When the above-mentioned metal nitride is a ferroelectric, the direction exhibiting ferroelectric polarization inversion is preferably oriented within 10 degrees from an axis perpendicular to the film surface. In other words, the polarization direction of the metal nitride layer 105 is preferably approximately perpendicular to the film surface. The crystal structure of the metal nitride layer 105 does not have centrosymmetrical properties, for example. The thickness of the metal nitride layer 105 is preferably 5 nm or more and 50 nm or less, for example.

[0030] The metal nitride layer 105 is formed by, for example, a sputtering method or an atomic layer deposition method. The sputtering method is preferable, and the atomic layer deposition method is more preferable. The manufacturing method of the metal nitride layer 105 (film) according to this embodiment includes a sputtering process. For example, in the case of a 3-inch target device, the sputtering process is performed by setting the DC voltage to 200 V or more, the DC current to 1 A or more, the gas pressure to 1 Pa or less, and the substrate temperature to room temperature to 400 degrees or less. When depositing under such conditions, as described in Non-Patent Document 1, it is possible to extend the mean free path of the deposited particles and form a film oriented in a substantially vertical direction. The same effect can be obtained with AC power.

[0031] The conductive layer 106 is provided on the metal nitride layer 105, and sandwiches the metal nitride layer 105 with the conductive layer 104. The conductive layer 106 is provided in contact with the metal nitride layer 105. The conductive layer 106 includes a conductive material. Examples of the conductive material include titanium nitride (TiN), titanium (Ti), tungsten nitride (WN), tungsten (W), tantalum nitride (TaN), and tantalum (Ta). The conductive layer 106 may be formed of the same conductive material as the conductive layer 104, or may be formed of a different conductive material. The conductive layer 104 and the conductive layer 106 function as electrodes for applying a voltage to the metal nitride layer 105.

[0032] The stack 20 including the conductive layer 104, the metal nitride layer 105, and the conductive layer 106 changes the resistance of the MTJ formed by the stack 10 as follows. First, a voltage is applied between the conductive layer 104 and the conductive layer 106. This induces an electric field in the metal nitride layer 105, which magnetizes the metal nitride layer 105. When the magnetization direction of the metal nitride layer 105 differs from the magnetization direction of the ferromagnetic layer 103, the magnetization direction of the ferromagnetic layer 103 is reversed. As a result, the resistance of the MJ element changes. The stack 20 is also an example of a stack according to this embodiment.

[0033] The metal nitride layer 105, together with the ferromagnetic layers 101 and 103, is a perpendicular magnetization film, and is magnetized in the perpendicular upward or downward direction.

[0034] The MTJ element 1 may include two or more metal nitride layers 105. The conductive layer 104 and the ferromagnetic layer 103 may be the same layer. That is, when the conductive layer 104 includes a ferromagnetic material and also functions as a magnetization free layer, the MTJ element 1 does not need to include the ferromagnetic layer 103. In this case, the conductive layer 104 is included in the stack 20 to change the resistance of the MTJ, and is also included in the stack 10 to form the MTJ.

[0035] The MTJ element 1 does not need to include the conductive layer 106. Even in this case, for example, a probe made of a nonmagnetic metal for AFM (Atomic Force Microscopy) arranged on the metal nitride layer 105 can be made to function as an electrode to apply an electric field to the metal nitride layer 105. That is, the stack 20 is required to include at least the metal nitride layer 105 and the conductive layer 104.

[0036] (MRAM) FIG. 2 is a cross-sectional view showing a single cell of the MRAM according to the embodiment. As shown in FIG. 2, the MRAM 2 according to the embodiment is a device, particularly a magnetic device, including the above-mentioned MTJ element 1. The MRAM 2 further includes a write word line 111, a bit line 112, a transistor 113, and a lower electrode substrate 114. The write word line 111 is connected to the conductive layer 104. The bit line 112 is connected to the lower electrode substrate 114 via the transistor 113. The transistor 113 is turned on by selecting the word line 115 connected to the gate. The lower electrode substrate 114 is provided on the ferromagnetic layer 101. The lower electrode substrate 114 functions as a wiring and is configured as a laminated film for fixing the magnetization of the ferromagnetic layer 101.

[0037] When reading digital information from the MRAM 2, the transistor 113 is turned on by selecting the write word line 111, and the digital information is read from the resistance value between the write word line 111 and the bit line 112. When writing digital information to the MRAM 2, the transistor 113 is turned on by selecting the write word line 111, and a voltage is applied between the write word line 111 and the conductive layer 106 to change the resistance of the MTJ and write the digital information. In other words, the metal nitride layer 105 is magnetized by applying a voltage, and the magnetization of the ferromagnetic layer 103 is reversed, thereby writing the digital information.

[0038] Since the MRAM 2 includes the above-mentioned MTJ element 1, it is possible to reduce the power consumption of the MTJ.

[0039] Although the embodiments have been described above, the present invention is not necessarily limited to the above-described embodiments, and various modifications are possible without departing from the gist of the present invention.

[0040] Although the MTJ element 1 is illustrated as an example of the element according to the embodiment, the element according to the embodiment may be, for example, a magnetic head, a magnetic memory, a magnetic sensor, a spin transistor, or a microwave oscillator. The element according to the embodiment may include at least a laminate of a film containing the metal nitride and a conductive layer. In addition, the MRAM 2, which is a magnetic device, is illustrated as an example of the device according to the embodiment, but the device according to the embodiment is not limited to the magnetic device and may include at least the element according to the embodiment as a component. For example, a structure having one function in a circuit is the element according to the embodiment, and a product made by combining the elements is the device according to the embodiment.

[0041] (Modification) FIG. 3 is a cross-sectional view showing an MTJ element according to a modified example. As shown in FIG. 3, the MTJ element 1A according to the modified example is different from the MTJ element 1 according to the embodiment in that the stack 20 further includes a protective layer 107. The protective layer 107 is an anti-oxidation layer that prevents oxidation of the metal nitride layer 105. The protective layer 107 covers the exposed surface of the metal nitride layer 105. The exposed surface of the metal nitride layer 105 is a portion of the surface of the metal nitride layer 105 that is exposed from other layers or members and may come into contact with the air. In the illustrated example, the protective layer 107 covers only the upper surface of the metal nitride layer 105 exposed from the conductive layer 106, but may also cover the side surface adjacent to the upper surface of the metal nitride layer 105.

[0042] The protective layer 107 includes, for example, amorphous silicon (a-Si). The a-Si is deposited, for example, by a sputtering method. Since a-Si is amorphous, it does not form grain boundaries and has high barrier performance. The barrier performance can be evaluated by common evaluation methods, such as the cup method, the pressure sensor method, and the calcium corrosion method. The thickness of the protective layer 107 is, for example, 50 nm or less, and may be 30 nm or less. By making the protective layer 107 thus thin, it is possible to suppress the occurrence of distortion and cracks due to stress.

[0043] The protective layer 107 may include, for example, an oxide of at least one metal element selected from the group consisting of Al, Si, and Ti, a nitride of the metal element, or an oxynitride of the metal element. These metal oxides, metal nitrides, and metal oxynitrides can be formed by, for example, a vapor phase deposition method. As the vapor phase deposition method, for example, a chemical vapor deposition method, an atomic layer deposition method, or a sputtering method can be used. The sputtering method can form a dense film with few grain boundaries. The protective layer 107 may have multiple layers. The protective layer 107 may include, for example, a layer containing a metal oxide and a layer containing a metal nitride, which are stacked together.

[0044] Conventionally, AlN-based materials are very stable materials and are thought not to be oxidized in the temperature range in which they are normally used. However, as a result of research and studies by the present inventors, it was found that the saturation magnetization of the metal nitride according to this embodiment decreases over time, and that the saturation magnetization of the metal oxynitride changes depending on the composition ratio of oxygen to nitrogen (O / N ratio) in the metal oxynitride. The present inventors hypothesized that the cause of deterioration over time is that oxygen penetrates into the metal oxynitride from the outside and replaces nitrogen, causing a change in the O / N ratio, and investigated a configuration that suppresses the penetration of oxygen from the outside. As a result, the present inventors found a configuration in which the metal nitride is covered with a protective layer that has the effect of suppressing oxidation.

[0045] The MTJ element 1A enables low power consumption of the MTJ, similarly to the MTJ element 1. The MTJ element 1A further includes the protective layer 107, which can prevent oxygen from penetrating into the metal nitride layer 105. This can prevent deterioration over time of the saturation magnetization of the metal nitride layer 105, and improve the driving durability and driving stability of the MTJ.

[0046] For example, the magnetic device made of the MRAM 2 may include an MTJ element 1A instead of the MTJ element 1. EXAMPLES

[0047] The present invention will be described below with reference to examples, but the present invention is not limited to the following examples.

[0048] (Experiment 1) In order to confirm that the above-mentioned metal oxide film is magnetized by an electric field, experiment 1 using an AFM was carried out as follows. 0.7 Sc 0.3 O 0.05 N 0.95 FIG. 4 is a diagram illustrating a method for evaluating the film. As shown in FIG. + An Al film (50 nm thick) is formed on the bottom surface of the Si substrate. + A TiN film (10 nm thick) is formed on the top surface of a Si substrate, and Al is then deposited on the TiN film. 0.7 Sc 0.3 O 0.05 N 0.95 A metal oxide film (15 nm thick) made of the following was formed to prepare a laminate according to the example. The Al film, the TiN film, and the metal nitride film were all formed by sputtering.

[0049] Then, using a 0.4T electromagnet, 0.7 Sc 0.3 O 0.05 N 0.95 The film was magnetized in the upward direction perpendicular to the film surface. Next, the TiN film was grounded, and the AFM probe P1 made of a non-magnetic metal was placed on the Al 0.7 Sc 0.3 O 0.05 N 0.95 Next, the probe P1 was placed in contact with the surface of the Al film. 0.7 Sc 0.3 O 0.05 N 0.95 A predetermined area (2 μm×2 μm area) on the film was scanned to write information. Figure 5(a) is an explanatory diagram of the write area and the write voltage.

[0050] After that, the AFM probe P1 made of a non-magnetic metal was changed to the MFM probe P2 made of a magnetic material, and Al 0.7 Sc 0.3 O 0.05N 0.95 The magnetization state of the film surface was confirmed without contact. Figure 5(b) is an MFM image showing the magnetization state after writing. As shown in Figure 5(b), in the area where writing was performed with the AFM probe P1, magnetization reversal according to the writing voltage was confirmed. When the writing voltage was set to ±9V, clear magnetization reversal was confirmed. All steps except for the process of forming the stack according to the embodiment were performed at room temperature (300K).

[0051] (Experiment 2) Experiment 2 was carried out using the laminate prepared in Experiment 1. In Experiment 2, Al 0.7 Sc 0.3 O 0.05 N 0.95 The magnetization direction of the film was perpendicular to the film, but the film was magnetized downward. The same procedure was used as in experiment 1. The AFM probe P1 was used to probe the Al 0.7 Sc 0.3 O 0.05 N 0.95 Information was written to the film, and the magnetization state was confirmed with the MFM probe P2. Although not shown, an MFM image almost identical to that in Figure 5(b) was obtained in Experiment 2. This shows that, regardless of the direction of the magnetization in advance, if the write voltage is set to ±9V, the magnetization state of Al 0.7 Sc 0.3 O 0.05 N 0.95 It was confirmed that the film could be magnetized.

[0052] (Experiment 3) Using the laminate prepared in Experiment 1, Experiment 3 was carried out at room temperature (300 K) as follows. First, an electromagnet of 0.4 T was used to 0.7 Sc 0.3 O 0.05 N 0.95 The film was magnetized in the upward direction perpendicular to the film surface. Next, the TiN film was grounded, and the AFM probe P1 made of a non-magnetic metal was placed on the Al 0.7 Sc 0.3 O 0.05 N 0.95 Next, a voltage of -9 V (corresponding to an electric field of -6 MV / cm) was applied to the AFM probe P1, and the Al 0.7 Sc 0.3 O 0.05N 0.95 A specified area (3 μm × 3 μm area) on the film was scanned and information was written. After that, the voltage was changed to +9 V (equivalent to an electric field of +6 MV / cm) and information was overwritten in a specified area (1 μm × 1 μm area) inside the area where the information was previously written. Figure 6(a) is an explanatory diagram of the writing area and the writing voltage.

[0053] Then, after writing, Al 0.7 Sc 0.3 O 0.05 N 0.95 The surface shape of the film was observed by AFM. Figure 6(b) is an AFM image showing the surface shape after writing. As shown in Figure 6(b), Al 0.7 Sc 0.3 O 0.05 N 0.95 It was found that the surface morphology of the film was not affected by the writing.

[0054] Next, the AFM probe P1 made of a non-magnetic metal was changed to the MFM probe P2 made of a magnetic material, and Al 0.7 Sc 0.3 O 0.05 N 0.95 The magnetization state of the film surface was confirmed without contact. Figure 6(c) is an MFM image showing the magnetization state after writing. As shown in Figure 6(c), the area where writing was performed with only -9V voltage turns light in color, and the area where overwriting was performed with +9V voltage turns dark in color. This shows that the Al 0.7 Sc 0.3 O 0.05 N 0.95 It was confirmed that the film allows not only one writing but also further magnetization reversal.

[0055] (Experiment 4) Experiment 4 was carried out at room temperature (300 K) using the laminate prepared in Experiment 1. In Experiment 4, Al 0.7 Sc 0.3 O 0.05 N 0.95The experiment was carried out in the same manner as in Experiment 3, except that the magnetization direction of the film was vertically downward. Although not shown in the figures, in Experiment 4, an AFM image almost similar to the AFM image in FIG. 6(b) and an MFM image almost similar to the MFM image in FIG. 6(c) were obtained. 0.7 Sc 0.3 O 0.05 N 0.95 It was confirmed that the surface shape of the film is not affected by writing, regardless of the direction of the previous magnetization, and that not only one writing but also further magnetization reversal is possible.

[0056] (Experiment 5) Experiment 5: Al 0.7 Sc 0.3 O y N 1-y A magnetic field was applied perpendicular to the film, and the magnetization curve (MH curve) was measured at room temperature (300 K). 0.7 Sc 0.3 O 0.05 N 0.95 1 is a graph showing the magnetization curve of the film. 0.7 Sc 0.3 O 0.05 N 0.95 A laminate was prepared by forming an AlN film (100 nm thick) and a TiN film (10 nm thick) in this order. Each film was formed by sputtering. The deposition of each film was carried out consecutively without exposing it to the outside air. 0.7 Sc 0.3 O 0.05 N 0.95 The magnetization curves of the Al films were measured. 0.7 Sc 0.3 O 0.2 N 0.8 1 is a graph showing the magnetization curve of a film. 0.7 Sc 0.3 O 0.2 N 0.8 A film (100 nm thick) was then formed. 0.7 Sc 0.3 O 0.2 N 0.8 The magnetization curve of the film was measured.

[0057] As shown in Fig. 7(a) and Fig. 7(b), it was confirmed that the magnetization increased by increasing the amount of oxygen in the perpendicular magnetic field. Although not shown, there was almost no magnetization in the in-plane magnetic field. 0.7 Sc 0.3 O y N 1-y The grain size of the film was about 30 nm in all cases. 0.7 Sc 0.3 O y N 1-y It is not believed to affect the magnetic properties of the film.

[0058] (Experiment 6) In experiment 6, Al was deposited by DC sputtering at different gas pressures. 0.7 Sc 0.3 O 0.05 N 0.95 The gas pressure was set to 0.7 Pa and 1.2 Pa, and the relationship between the ferroelectric properties of the films and the orientation state was investigated.

[0059] Figure 8 shows the results of X-ray diffraction (XRD) of the AlScN film. Here, the lattice plane parallel to the film surface was measured by the out-of-plane method. As shown in Figure 8, it can be confirmed that the (002) orientation (c-axis) of the AlScN film has better ferromagnetic properties than the (100) orientation. It can also be confirmed that the film deposited at a gas pressure of 0.7 Pa has more (002) components and has better orientation than the film deposited at a gas pressure of 1.2 Pa. In other words, the orientation of the film can be controlled by the gas pressure in the deposition process, and when deposited at 0.7 Pa, a film with a (002) orientation can be obtained. As a result, a ferromagnetic film suitable for an MTJ element can be obtained.

[0060] In Non-Patent Document 1, it is speculated that the reason why the (002) component increases as the pressure decreases during high-frequency sputtering of aluminum nitride (AlN) is that the mean free path becomes longer and the mobility of adatoms increases. For these reasons, it may be easier to obtain a ferroelectric film by using a low gas pressure.

[0061] (Experiment 7) In order to confirm the correlation between the saturation magnetization and the O / N ratio of the metal oxynitride, samples were prepared, their magnetic properties were evaluated, and their compositions were analyzed by the following methods.

[0062] (1) Sample preparation n + An electrode layer (10 nm thick) made of TiN film is formed on a Si substrate, and Al is then deposited on the electrode layer. 0.7 Sc 0.3 O y N 1-y A metal oxynitride layer (100 nm thick) made of a film was formed to prepare a laminate according to the example. The TiN film was formed by RF sputtering using a Ti target at a substrate temperature of 400° C., a deposition pressure of 0.3 Pa, Ar and N 2 were introduced at a flow ratio of 2:3, and discharged at 300 W. Al 0.7 Sc 0.3 O y N 1-y The film was formed by DC sputtering using an AlSc (composition ratio 53:47) target at a substrate temperature of 400°C and a film formation pressure of 0.5 Pa. Ar, N2, and O2 were introduced at a flow rate ratio of 5:10:y, and discharged at 300 W. y=0, 0.1, 0.2, 0.3, 0.4, and 0.5. (2) Magnetic property evaluation The magnetic properties of the metal oxynitride film were evaluated using a magnetic property evaluation system manufactured by Quantum Design, Inc., USA. (3) Composition analysis The composition ratio of the metal oxynitride film can be quantified by XPS analysis. A PHI Quantera SXM was used as the measuring device, and the evaluation was performed with a detection area of ​​100 μmφ. The composition ratio was calculated from the spectral intensities of Al2p, Sc2p, N1s, and O1s.

[0063] Figure 9 shows the Al 0.7 Sc 0.3 O y N 1-y9 is a graph showing the magnetization curve of the film. FIG. 10 is a graph showing the relationship between the oxygen substitution amount and the saturation magnetization amount. As shown in FIG. 9 and FIG. 10, it was found that the magnetic properties were improved by substituting a part of the N in AlScN with O. The saturation magnetization amount was maximum when O / (O+N)~0.2 (i.e., y~0.2). It was found that magnetization could be obtained up to O / (O+N)~0.4 (i.e., y~0.4).

[0064] (Experiment 8) In order to confirm the correlation between the application of a protective layer to a metal oxynitride layer and deterioration over time, samples were prepared and their magnetic properties were evaluated by the following method.

[0065] (1) Sample preparation n + An electrode layer (10 nm thick) made of TiN film is formed on a Si substrate, and Al is then deposited on the electrode layer. 0.7 Sc 0.3 O 0.3 N 0.7 A metal oxynitride layer (100 nm thick) made of a film was formed, and a protective layer was further formed on the metal oxynitride film to prepare a laminate according to the embodiment. The protective layer was an a-Si film (30 nm thick), a TiN film (30 nm thick), a SiN film (100 nm thick), or a fluororesin film (100 nm thick). For comparison, a laminate without a protective layer was also prepared. The TiN film was formed by RF sputtering using a Ti target at a substrate temperature of 400° C., a deposition pressure of 0.3 Pa, Ar and N 2 were introduced at a flow ratio of 2:3, and discharged at 300 W. Al 0.7 Sc 0.3 O 0.3 N 0.7 The film was deposited by DC sputtering using an AlSc (composition ratio 53:47) target at a substrate temperature of 400°C and a deposition pressure of 1.5 Pa. Ar, N2, and O2 were introduced at a flow rate ratio of 5:10:0.3, and discharged at 300 W. The a-Si film was formed by RF sputtering using a Si target at a substrate temperature of 400° C., with Ar introduced so as to set the film formation pressure at 0.5 Pa, and discharged at 150 W. The SiN film was formed by plasma enhanced chemical vapor deposition using a parallel plate type apparatus, with trisilylamine as the raw material and nitrogen gas introduced. The substrate temperature was 200°C, the film formation pressure was 30 Pa, the flow rate of trisilylamine was 0.6 sccm, the flow rate of nitrogen gas was 100 scc, and the RF power was 100 W. The fluororesin film was formed by introducing trifluoromethane using a plasma chemical vapor deposition method with a parallel plate type device. The substrate temperature was room temperature, the film formation pressure was 80 Pa, the flow rate of trifluoromethane was 80 sccm, and the RF power was 30 W. (2) Magnetic property evaluation The magnetic properties of the metal oxynitride films were evaluated using a magnetic properties evaluation system manufactured by Quantum Design, Inc., USA. The relationship between the number of days of exposure to the atmosphere and the amount of magnetization was calculated based on the saturation magnetization measured immediately after the start of exposure to the atmosphere. The samples were stored in a vacuum from the time of sample preparation until the first evaluation (i.e., the evaluation of the magnetic properties immediately after the start of exposure to the atmosphere).

[0066] FIG. 11 is a graph showing the change in saturation magnetization over time. The saturation magnetization is shown as a percentage based on the saturation magnetization measured immediately after the start of air exposure. FIG. 11 shows the change in saturation magnetization over time for each of the cases where there is no protective layer, where the protective layer is an a-Si film, where the protective layer is a TiN film, where the protective layer is a SiN film, and where the protective layer is a fluororesin film. As shown in FIG. 11, it was confirmed that the deterioration of magnetic properties can be suppressed by covering the AlScON film with an a-Si film, a SiN film, or a TiN film. Since the gas permeability of organic materials is higher than that of inorganic materials, it is considered that the magnetic properties deteriorated faster in the case of the fluororesin film than in the case of other protective layers. The reason why the magnetic properties deteriorated faster in the case of the fluororesin film than in the case of the no protective layer is not clear, but possible reasons include damage to the metal oxynitride layer during the formation of the fluororesin film, reaction between the fluororesin film and the metal oxynitride layer, and deterioration of the fluororesin film due to air exposure.

[0067] [Additional remarks] The metal nitride, film, laminate, element, device, film manufacturing method, magnetic tunnel junction element, and magnetic device disclosed herein enable low power consumption, and can contribute to the achievement of Goal 9 of the Sustainable Development Goals (SDGs) led by the United Nations. Goal 9: "Build infrastructure for industry and innovation" [Explanation of symbols]

[0068] 1,1A...MTJ element (element), 2...MRAM (device, magnetic device), 20...laminated body, 101...ferromagnetic layer (first ferromagnetic layer), 102...tunnel insulating layer, 103...ferromagnetic layer (second ferromagnetic layer), 104...conductive layer (second conductive layer), 105...metal nitride layer (film), 106...conductive layer (first conductive layer), 107...protective layer.

Claims

1. It has a wurtzite structure, General formula Z 1-x M x W y N 1-y It is expressed as Z is at least one element selected from the group consisting of Al, In, and Ga; M is at least one element selected from the group consisting of Sc, B, Gd, Cr, Zn, Y, La, Ce, Pr, Nd, Sm, Eu, Tb, Dy, Ho, Er, Tm, Yb, Ti, Hf, and Zr; W is at least one element selected from the group consisting of O, S, Se, F, Cl, Br, and I; 0<x≦0.45 and 0<y≦0.4; It is not an n-type semiconductor. Metal nitrides.

2. The metal nitride of claim 1 , wherein Z is Al.

3. The metal nitride of claim 1 , wherein Z is In.

4. The metal nitride of claim 1 , wherein Z is Ga.

5. The metal nitride according to any one of claims 1 to 4, wherein M is Sc.

6. The metal nitride according to any one of claims 1 to 4, wherein M is B.

7. The metal nitride according to any one of claims 1 to 4, wherein W is O.

8. The metal nitride according to any one of claims 1 to 4, wherein W is S.

9. The metal nitride according to any one of claims 1 to 4, wherein W is Se.

10. A film comprising the metal nitride according to any one of claims 1 to 4.

11. A membrane according to claim 10; and a conductive layer provided on the film.

12. A device comprising the laminate according to claim 11.

13. A device comprising the element of claim 12.

14. A method for producing the membrane according to claim 10, comprising the steps of: A method for producing a film, comprising a sputtering step.

15. a first ferromagnetic layer which is a magnetization fixed layer; a second ferromagnetic layer which is a magnetization free layer; a tunnel insulating layer interposed between the first ferromagnetic layer and the second ferromagnetic layer; a metal nitride layer provided on the second ferromagnetic layer; a first conductive layer provided on the metal nitride layer; The metal nitride layer is a film containing a metal nitride, It has a wurtzite structure, General formula Z 1-x M x W y N 1-y It is expressed as Z is at least one element selected from the group consisting of Al, In, and Ga; M is at least one element selected from the group consisting of Sc, B, C, Si, Gd, Cr, Zn, Y, La, Ce, Pr, Nd, Sm, Eu, Tb, Dy, Ho, Er, Tm, Yb, Ti, Hf, and Zr; W is at least one element selected from the group consisting of O, S, Se, F, Cl, Br, and I; 0<x≦0.45 and 0<y≦0.4; Magnetic tunnel junction element.

16. The magnetic tunnel junction element of claim 15 , wherein Z is Al.

17. The magnetic tunnel junction element of claim 15 , wherein Z is In.

18. The magnetic tunnel junction element of claim 15 , wherein Z is Ga.

19. The magnetic tunnel junction element according to any one of claims 15 to 18, further comprising a second conductive layer provided between the second ferromagnetic layer and the metal nitride layer.

20. A magnetic device comprising the magnetic tunnel junction element according to any one of claims 15 to 18.

21. The magnetic device of claim 10 which is a magnetic random access memory.

22. A film including a metal nitride; A protective layer covering the surface of the film; The metal nitride is It has a wurtzite structure, General formula Z 1-x M x W y N 1-y It is expressed as Z is at least one element selected from the group consisting of Al, In, and Ga; M is at least one element selected from the group consisting of Sc, B, C, Si, Gd, Cr, Zn, Y, La, Ce, Pr, Nd, Sm, Eu, Tb, Dy, Ho, Er, Tm, Yb, Ti, Hf, and Zr; W is at least one element selected from the group consisting of O, S, Se, F, Cl, Br, and I; 0<x≦0.45 and 0<y≦0.4; the protective layer contains at least one oxide of a metal element selected from the group consisting of Al, Si, and Ti, a nitride of the metal element, an oxynitride of the metal element, or amorphous silicon; Laminate.

23. 23. The laminate of claim 22, wherein Z is Al.

24. 23. The stack of claim 22, wherein Z is In.

25. 23. The stack of claim 22, wherein Z is Ga.

26. A magnetic device comprising the laminate according to any one of claims 22 to 25.

Citation Information

Patent Citations

  • n-TYPE ALN CRYSTAL AND METHOD FOR MANUFACTURING THE SAME

    JP2007261883A

  • Magnetic tunnel junction element and magnetic memory

    JP2014229706A

  • Magnetic tunnel junction element and magnetoresistive memory device

    JP2022069247A